Evaluation of the Cytotoxic Activity of the Usnea barbata (L.) F. H. Wigg Dry Extract - Violeta Popovici; Laura Adriana Bucur; Verginica Schröder; Daniela Gherghel; Cosmin Teodor Mihai; Aureliana Caraiane; Florin Ciprian Badea; Gabriela Vochița; Victoria Badea (Molecules, 2020)
The secondary metabolites of lichens have proven to be promising sources of anticancer drugs; one of the most important of these is usnic acid, which is a phenolic compound with dibenzofuran structure that is responsible for the numerous biological actions of lichens of genus Usnea. As a result, in this study, we related to this phenolic secondary metabolite. The aim of the present study is the evaluation of the cytotoxic activity of Usnea barbata (L.) F. H. Wigg dry acetone extract (UBE). In advance, the usnic acid content was determined in various extracts of Usnea barbata (L.) F. H. Wigg: the liquid extracts were found in water, ethanol, acetone, and the dry acetone extract; the highest usnic acid quantity was found in the dry acetone extract. First, the cytotoxic action of UBE was assessed using Brine Shrimp Lethality (BSL) test; a significant lethal effect was obtained after 24 h of treatment at high used concentrations of UBE, and it was quantified by the high mortality rate of the Artemia salina (L.) larvae. Secondly, in vitro cytotoxicity of UBE was evaluated on human tongue squamous cells carcinoma, using CAL 27 (ATCC® CRL-2095™) cell line. The most intense cytotoxic effect of UBE on CAL 27 cells was registered after 24 h; this response is directly proportional with the tested UBE concentrations. The obtained results have been reported regarding usnic acid content of UBE, and the data show that CAL 27 cells death was induced by apoptosis and high oxidative stress.